2020
DOI: 10.1093/ehjci/jez319.1136
|View full text |Cite
|
Sign up to set email alerts
|

P1780 Left ventricular golbal longitudinal strain in acute myocardial infarction and incidence of in hospital heart failure

Abstract: Background The occurrence of in-hospital heart failure in the acute phase of myocardial infarction carries an ominous prognosis and is often preceded by abrupt loss of functioning myocardium. However ,In hospital heart failure may occur in patients with apparently only minor myocardial injury and preserved or only moderately reduced left ventricular ejection fraction and still carries a significantly increased risk of adverse outcome. In patients with clinical symptoms of heart failure despit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These results are emphasizing the increasing value of 2D-STE in assessing the LV function in AMI patients and are concordant with those of other recently published studies. 29,35 The identified cut-off levels predicting LV remodeling at baseline echocardiographic examination were −11% for HLS and −0.65 s −1 for HLSR. A baseline HLS < -11% increased the hazard ratio for LV remodeling by a factor of 1.4, while the AMI patients with a baseline HLSR< −0.65s −1 were 2.16 more likely to develop LV remodeling (P<0.001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are emphasizing the increasing value of 2D-STE in assessing the LV function in AMI patients and are concordant with those of other recently published studies. 29,35 The identified cut-off levels predicting LV remodeling at baseline echocardiographic examination were −11% for HLS and −0.65 s −1 for HLSR. A baseline HLS < -11% increased the hazard ratio for LV remodeling by a factor of 1.4, while the AMI patients with a baseline HLSR< −0.65s −1 were 2.16 more likely to develop LV remodeling (P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…It proved to be superior to LVEF and WMIS especially in AMI patients with an LVEF >40%. 29 Ersbøll demonstrated that a reduced GLS was significantly associated with augmented neuro-hormonal activation, early hemodynamic aggravation, and prediction of a poor outcome in AMI with preserved LVEF. Early measurement of GLS in this population could be used as a risk stratification tool for added monitoring and clinical trials.…”
Section: Discussionmentioning
confidence: 99%